Exploring Cross-Border Cultural Policy in Practice, Special Issue Introduction - Durrer, Victoria; Corrigan, Jordana; Munck, Ronaldo (Irish Journal of Arts Management and Cultural Policy, 2019)
This article is an introduction to the Special Issue: Exploring Cross-Border Cultural Policy in Practice. It outlines the importance of considering cultural policy on the island of Ireland in a cross-border context and reflects on learning gained from an event on the subject co-organised by Cultural Policy Observatory Ireland, the Social Innovation Network and Dublin City University at The Garage Theatre in Monaghan in November 2018.